A Study on IL-1 Receptor Antagonist/IL-1.ALPHA. Ratio in the Stratum Corneum of the So-called Sensitive Skin - HARIYA Takeshi; HIRAO Tetsuji; YOKOYAMA Tomoko; ICHIKAWA Hideyuki (Skin research, 2001)
In the female subjects with the so-called sensitive skin, we measured IL-1 receptor antagonist (IL-1ra)/IL-1α ratio (ra/a ratio) in the stratum corneum and studied the relationship between skin physiological parameters and ra/α ratio. As a result, ra/α ratio correlated with the values of TEWL and the size of corneocyte. These results suggest that ra/α ratio is related with disordered barrier function and the rate of turn overin the stratum corneum. Ra/α ratio of two types of subjects with sensitive skin was higher than that of control subjects. And, high level of ra/α ratio of subjects with sensitive skin was improved by using a series of skin care products. As these results, we suggestedthat ra/α ratio was a novel parameter of sensitive skin. いわゆる敏感肌女性のIL-1receptor antagonist (IL-1ra)/IL-1α の比 (ra/αratio) を測定し, 皮膚生理指標との相関性を検討した.その結果, ra/αratioはTEWLと正の相関を, 角層細胞サイズと負の相関を示し, 角層バリア機能の低下や角層ターンオーバー速度との関連性が示唆された.また, 敏感肌を肌質から2つのタイプに分けてra/α ratioを測定した結果, 両敏感肌群とも健常肌群よりも有意に高値を示した.さらに, いわゆる敏感肌女性に対してスキンケアを実施した結果, 高値を示したra/αratioは有意に低下した.以上より, ra/ αratioは敏感肌の1つの新しい指標になることが示唆された.